2020
DOI: 10.7717/peerj.9124
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the bacterial microbiota composition and evolution at different intestinal tract in wild pigs (Sus scrofa ussuricus)

Abstract: Commensal microorganisms are essential to the normal development and function of many aspects of animal biology, including digestion, nutrient absorption, immunological development, behaviors, and evolution. The specific microbial composition and evolution of the intestinal tracts of wild pigs remain poorly characterized. This study therefore sought to assess the composition, distribution, and evolution of the intestinal microbiome of wild pigs. For these analyses, 16S rRNA V3-V4 regions from five gut sections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 64 publications
4
13
0
Order By: Relevance
“…Firmicutes, Bacteroidetes, Proteobacteria, Actinobacteria, Verrucomicrobia, Fusobacteria, and Spirochetes were the major phyla in gastrointestinal system of wild boar. This is similar to the gut microbiota distribution of most mammals such as domestic pigs, captive wild boars, Hainan special wild boar, snubnosed monkey (Rhinopithecus bieti), and moose (Alces alces) (Ishaq and Wright 2014;Wang et al 2020;Wu et al 2010;Yang et al 2020;Yang et al 2016). Firmicutes and Bacteroidetes are widely present in herbivorous animals, especially in ungulates.…”
Section: Gut Microbiota Of Wild Boar and Comparison With Other Ungulatessupporting
confidence: 67%
See 1 more Smart Citation
“…Firmicutes, Bacteroidetes, Proteobacteria, Actinobacteria, Verrucomicrobia, Fusobacteria, and Spirochetes were the major phyla in gastrointestinal system of wild boar. This is similar to the gut microbiota distribution of most mammals such as domestic pigs, captive wild boars, Hainan special wild boar, snubnosed monkey (Rhinopithecus bieti), and moose (Alces alces) (Ishaq and Wright 2014;Wang et al 2020;Wu et al 2010;Yang et al 2020;Yang et al 2016). Firmicutes and Bacteroidetes are widely present in herbivorous animals, especially in ungulates.…”
Section: Gut Microbiota Of Wild Boar and Comparison With Other Ungulatessupporting
confidence: 67%
“…It is also of great significance in metabolism, immune regulation and a variety of gut diseases (Chi et al 2014;Huang et al 2018;Xiong et al 2015;Zhu et al 2016). In our study, a total of 394 genera, 160 families, 23 phyla were identified, and the abundance and diversity of microbiota were higher than those of the captive wild boars and domestic pigs from Xinyang County, Henan Province (163 genera, 17 phyla) and Chongqing City (118 genera, 13 phyla) (Wang et al 2020;Yang et al 2020;Yang et al 2016). This may be due to the difference in gut microbiota caused by different breeds (Huang et al 2020), or the difference between captive and wild environments.…”
Section: The Microbiota Diversity Of Wild Boar and Comparison With Ot...mentioning
confidence: 61%
“…This is related to the high abundance of Ruminococcaceae_UCG-005, Prevotella_7 and Chris-tensenellaceae_R-7_group, which requires anaerobic conditions and carbohydrate energy sources in dietary bers (such as cellulose or xylan). Similar functions have been found in the captive wild boar (Yang 2020). This study suggests that microbes in the small intestine are more inclined to quickly digest, absorb simple carbohydrates such as glucose and maltose.…”
Section: Gut Microbiota and Function Predictionsupporting
confidence: 80%
“…It is also of great signi cance in metabolism, immune regulation and a variety of gut diseases (Chi et Huang et al 2018). In our study, a total of 394 genera, 160 families, 23 phyla were identi ed, and the abundance and diversity of microbiota were higher than those of the captive wild boars and domestic pigs from Xinyang County, Henan Province (163 genera, 17 phyla) and Chongqing City (118 genera, 13 phyla)(Wang 2020, Yang et al 2016, Yang et al 2020). This may be due to the difference in gut microbiota caused by different breeds (Huang 2020), or the difference between captive and wild environments.…”
Section: The Microbiota Diversity Of Wild Boar and Comparison With Other Ungulatesmentioning
confidence: 71%
“…Actinobacteria were mainly distributed in the stomach of herbivores, and they promote fiber decomposition and help in the digestive function of these animals (22). It is noteworthy that Actinobacteria was dominant phylum in Tibetan piglets, which was identified with predecessor's research in wild pigs (23). This phenomenon may be related to the herbivorous nature of Tibetan piglets.…”
Section: Discussionmentioning
confidence: 92%